Differential gene expression provides leads to environmentally regulated soybean seed protein content - Hooker, Julia C.; Smith, Myron; Zapata, Gerardo; Charette, Martin; Luckert, Doris; Mohr, Ramona M.; Daba, Ketema A.; Warkentin, Thomas D.; Hadinezhad, Mehri; Barlow, Brent; Hou, Anfu; Lefebvre, François; et al. (Frontiers in Plant Science, 2023)
Soybean is an important global source of plant-based protein. A persistent trend has been observed over the past two decades that soybeans grown in western Canada have lower seed protein content than soybeans grown in eastern Canada. In this study, ten soybean genotypes ranging in average seed protein content were grown in an eastern (control) and three western (experimental) locations in Canada. Seed protein and oil content were measured for all lines in each location. RNA-sequencing and differential gene expression analysis was used to identify differentially expressed genes that may account for relatively low protein content in western-grown soybeans. Differentially expressed genes were enriched for ontologies and pathways that included amino acid biosynthesis, circadian rhythm, starch metabolism and lipid biosynthesis. Gene ontology, pathway mapping and QTL mapping collectively provide a close inspection into mechanisms influencing nitrogen assimilation and amino acid biosynthesis between soybeans grown in East and West. It was found that western-grown soybeans had persistent upregulation of asparaginase (an asparagine hydrolase), and persistent downregulation of asparagine synthetase across 30 individual differential expression datasets. This specific difference in asparagine metabolism between growing environments is almost certainly related to the observed differences in seed protein content because of the positive correlation between seed protein content at maturity and free asparagine in the developing seed. These results provided 2 This is a provisional file, not the final typeset article pointed information on seed protein-related genes influenced by environment. This information is valuable for breeding programs and genetic engineering of geographically-optimized soybean.